Road injuries and relaxed licensing requirements for driving light motorcycles in Spain: a time-series analysis - Katherine Pérez; Marc Marí-Dell'Olmo; Carme Borrell Manel Nebot; Joan R Villalbí; Elena Santamariña (The World Health Organization, 2009)
OBJECTIVE: To assess differences between the risk of injury for motorcycle riders before and after the passing of a law allowing licenced car drivers to drive light motorcycles without having to take a special motorcycle driving test. METHODS: We carried out a quasi-experimental study involving comparison groups, and a time-series analysis from 1 January 2002 to 30 April 2008. The study group was composed of people injured while driving or riding a light motorcycle (engine capacity 51-125 cubic centimetres), while the comparison groups consisted of riders of heavy motorcycles (engine capacity > 125 cc), mopeds (engine capacity <50 cc) or cars who were injured in a collision within the city limits. The "intervention" was a law passed in October 2004 allowing car drivers to drive light motorcycles without taking a special driving test. To detect and quantify changes over time we used Poisson regression, with adjustments for trend and seasonality in road injuries and the existence of a driver's licence penalty point system. FINDINGS: The risk of injury among light motorcycle riders was greater after the law than before (relative risk, RR = 1.46; 95% confidence interval, CI: 1.34-1.60). Although less markedly, after the law the risk of injury also increased among heavy motorcycle drivers (RR = 1.15; 95% CI: 1.02-1.29) but remained unchanged among riders of mopeds (RR = 0.92; 95% CI: 0.83-1.01) and cars (RR = 1.06; 95% CI: 0.97-1.16). CONCLUSION: Allowing car drivers to drive motorcycles without passing a special test increases the number of road injuries from motorcycle accidents.